Pengadaan Koleksi Muatan Lokal â€œLocal Content â€sebagai Upaya Pelestarian Budaya Daerah di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Putri, Cici Anjelina; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThe writing of this paper aims to describe: (1) local content collection services, (2) constraints in procuring local content collections; and (3) efforts in procuring local content collections in the Archives Service and West Sumatra Province Library. The method of writing this paper is to use a qualitative descriptive method which is done by observation, interviews and data collection directly to the source, the Office of Archives and the Library of West Sumatra Province. Based on the results of interviews and observations conducted at the Archives Service and West Sumatra Province Library are as follows: First, the service collection of